2020
DOI: 10.1021/acsami.0c15816
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Tunable Self-Powered UV Photodetectors Driven Jointly by p-n Junction and Ferroelectric Polarization

Abstract: Ferroelectric (FE) materials are thought to be promising materials for self-powered ultraviolet (UV) photodetector applications because of their photovoltaic effects. However, FE-based photodetectors exhibited poor performance because of the weak photovoltaic effect of FE depolarization field (E dp) on the separation of photo-generated carriers. In this work, self-powered photodetectors based on both E dp and built-in electric field at the p-n junction (E p‑n) were designed to obtain enhanced device performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…[14][15][16] For ferroelectric-based self-powered UV photodetectors, the ferroelectric depolarization electric field (E dp ) and the built-in electric field at the ferroelectric/electrode interface are the main driven force of photogenerated carriers. [6,17,18] However, the device performance of so far reported ferroelectric-based self-powered UV photodetectors is yet inferior, owing to the limited photogenerated carriers separation ability of ferroelectric depolarization electric field. [17] For example, responsivities (R) of these detectors are on the order of 10 −7 -10 −4 A W −1 , which are much lower than those of the semiconductor-based detectors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16] For ferroelectric-based self-powered UV photodetectors, the ferroelectric depolarization electric field (E dp ) and the built-in electric field at the ferroelectric/electrode interface are the main driven force of photogenerated carriers. [6,17,18] However, the device performance of so far reported ferroelectric-based self-powered UV photodetectors is yet inferior, owing to the limited photogenerated carriers separation ability of ferroelectric depolarization electric field. [17] For example, responsivities (R) of these detectors are on the order of 10 −7 -10 −4 A W −1 , which are much lower than those of the semiconductor-based detectors.…”
mentioning
confidence: 99%
“…[6,17,18] However, the device performance of so far reported ferroelectric-based self-powered UV photodetectors is yet inferior, owing to the limited photogenerated carriers separation ability of ferroelectric depolarization electric field. [17] For example, responsivities (R) of these detectors are on the order of 10 −7 -10 −4 A W −1 , which are much lower than those of the semiconductor-based detectors. [17,[19][20][21][22][23] Thus, it's highly demanding to further optimize the device performance of ferroelectric-based self-powered UV detectors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups recently demonstrated self‐powered heterojunction UV PDs. [ 22–24 ] Chen et al [ 25 ] reported a self‐powered PD based on NiO and a ferroelectric (FE) material (Pb 0.95 La 0.54 Ti 0.46 O 3 ) with a responsivity of 0.18 mA W −1 and a low dark current of 1.3 pA. The device performance enhancement was mainly due to the combined FE depolarization field and the built‐in field.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] In addition, the high remanent polarization of the ferroelectric gate materials ensures a high gate electric field in such devices even after the removal of the gate voltage. The previously developed ferroelectric-gated photodetectors based on bulk ZnO/BaTiO 3 [26] and NiO/ Pb 0.95 La 0.05 Zr 0.54 Ti 0.46 O 3 [27] heterostructures typically possess low photoresponsivity of the order of 10 À3 A W À1 . The reported ferroelectric-gated photodetectors with 2D channel materials, such as MoS 2 [28] and In 2 Se 3 , [29] engage ferroelectric polymer top gate, which adds complexity in device fabrication.…”
Section: Introductionmentioning
confidence: 99%